2011
DOI: 10.1155/2011/271694
|View full text |Cite
|
Sign up to set email alerts
|

Murine Models of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a multifactorial autoimmune disorder. The study of diverse mouse models of lupus has provided clues to the etiology of SLE. Spontaneous mouse models of lupus have led to identification of numerous susceptibility loci from which several candidate genes have emerged. Meanwhile, induced models of lupus have provided insight into the role of environmental factors in lupus pathogenesis as well as provided a better understanding of cellular mechanisms involved in the onset and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
286
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(310 citation statements)
references
References 182 publications
6
286
2
6
Order By: Relevance
“…This apparent discrepancy might be due to genetic background differences between the lupus mice models used in each study conferring distinctive characteristics to each model [39]. Although CO could modulate CD11b 1 cell expansion in spleen from lupus FcgRIIb KO mice, CO treatment in MRL-Fas lpr lupus mice does not modulate this cell type population.…”
mentioning
confidence: 97%
“…This apparent discrepancy might be due to genetic background differences between the lupus mice models used in each study conferring distinctive characteristics to each model [39]. Although CO could modulate CD11b 1 cell expansion in spleen from lupus FcgRIIb KO mice, CO treatment in MRL-Fas lpr lupus mice does not modulate this cell type population.…”
mentioning
confidence: 97%
“…Spontaneous lupus arises in BSXB/Yaa and MRL/lpr mouse strains, as well as from F1 hybrids between New Zealand White (NZW) and New Zealand Black (NZB) strains. These strains have predominantly been used to shed light on the genetic factors contributing to the development of SLE (172).…”
Section: Type III Hypersensitivitymentioning
confidence: 99%
“…The exact etiology of SLE is unknown, and mouse models with the development of lupus-like phenotypes have been crucial to uncovering cellular and genetic mechanisms of disease. Spontaneous (NZB/W F1, MRL/lps, BXSB/ Yaa) and induced (pristine and chronic graft-versus-host disease) mouse models of lupus have led to the identification of numerous susceptibility loci and provided identification of potential biomarkers for disease and prognosis [134]. Indeed, extensive animal and human studies have revealed a crucial role for type I IFN in the initiation and perpetuation of disease, and components of the IFN system, including transcription factors, are now putative drug targets and biomarkers in the treatment of SLE.…”
Section: Ifns In Systemic Lupus Erythematosusmentioning
confidence: 99%